2012
DOI: 10.3109/09637486.2012.700922
|View full text |Cite
|
Sign up to set email alerts
|

The effect of apparent amylose content and dietary fibre on the glycemic response of different varieties of cooked milled and brown rice

Abstract: Brown rice is a good source of dietary fibre (DF) and contains higher vitamins/minerals than milled rice. The study determined the effect of amylose content (AC) and DF on glucose response (GR) from different varieties of milled and brown rice. Milled and brown rice were used as test foods. They were fed to 9-10 human volunteers containing 50 g available carbohydrate after an overnight fast. GR and the glycemic index (GI) were determined. Results found that Sinandomeng with the lowest AC had a high GI = 75, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 17 publications
2
63
0
1
Order By: Relevance
“…The stark colour contrasts between coloured rice and viands (except for braised meats, which mostly have dark sauces, and for risotto, still a foreign concept) may also turn consumers off. However, unmilled rice is known to contain more nutrients and fibre than milled rice (Trinidad et al, 2013, Villareal et al, 1991), while dark pigments in the bran are associated with biomedical properties (reviewed in Rahman et al, 2016). The experts, therefore, must have included health-improving properties in defining premium rice 2.…”
Section: Resultsmentioning
confidence: 99%
“…The stark colour contrasts between coloured rice and viands (except for braised meats, which mostly have dark sauces, and for risotto, still a foreign concept) may also turn consumers off. However, unmilled rice is known to contain more nutrients and fibre than milled rice (Trinidad et al, 2013, Villareal et al, 1991), while dark pigments in the bran are associated with biomedical properties (reviewed in Rahman et al, 2016). The experts, therefore, must have included health-improving properties in defining premium rice 2.…”
Section: Resultsmentioning
confidence: 99%
“…It appears that under elevated [CO 2 ] in the present study, carbohydrate pools in the vegetative tissues were all affected, whereas in the grains only free sugars were affected. Rice pasting properties depend primarily on the rupture of starch granules and the release of soluble amylose (Bett-Garber et al 2013;Trinidad et al 2013). Calculated data suggest that nearly 50% of the calories that humans consume are derived from starch (Högy et al 2009).…”
Section: Effect Of Elevated [Co 2 ] On Rice Free Sugars Starch and mentioning
confidence: 99%
“…From Table IV, it can be observed that approximately 80% of white rice consisted of starch, compared with 74% for the brown rice. Effects of elevated [CO 2 ] on the amylose content are therefore commercially important because low amylose content mirrors increased viscosity and softness (Terao et al 2005;Yang et al 2007;Trinidad et al 2013) (Table IV). Given the results obtained here and those reported by other authors, it remains inconclusive if that supply of the starch-based industry will be affected in a near future when the global atmospheric [CO 2 ] reaches 550 μmol/mol.…”
Section: Effect Of Elevated [Co 2 ] On Rice Free Sugars Starch and mentioning
confidence: 99%
See 1 more Smart Citation
“…Brown rice (IR64) with 23% available carbohydrates and dietary fibers of 2.5 g/100 g had a low GI = 51. 74 Cell wall integrity and cellular structure change with the ripening process, and GI in turn increases with ripening. Green bananas have a high content of RS, and only a negligible amount remains after ripening.…”
Section: Processing Conditionsmentioning
confidence: 99%